Cyber Security in Cloud Computing Environments: Risks & Solutions - Ravindra, M G (Digital Repository of Theses, 2026)
This research project examines significant security threats to cloud computing services and tests various protective tools to determine which ones most effectively address these issues. Our primary objective is to analyse how combining data encryption (DE), access control (AC), and Intrusion Detection Systems (IDS) enhances cloud security compliance and performance. The study employs structured questionnaires to gather responses from 300 experts, including IT professionals, cybersecurity specialists, and cloud service providers (CSPs). Participants were selected through convenience sampling due to their professional expertise in securing cloud systems (CS). Fixed response questions are used in the survey to collect precise data on security features, including encryption methods, access permission and IDA. Descriptive statistics and inferential analysis findings were generated by using the Statistical Package for the Social Sciences (SPSS) for the data analysis. Our findings indicate that data encryption protects against unauthorised access and data loss, while IDA effectively prevent malware attacks and data theft. Access control in a fully integrated security system demonstrates its ability to shield organisations from insider threats and credential theft. Overall, security solutions that work in tandem offer enhanced cloud protection and help organisations meet their security requirements. Robust security systems protect data integrity, ensure regulatory compliance, and mitigate advanced internet threats, leading to increased trust and improved performance in cloudbased environments. These results are significant for security practitioners across multiple industries and for cloud security researchers, who will benefit from the detailed insights this study provides. Our research contributes new perspectives on cloud security by examining the interplay between cloud threats, security tools, and system performance. Keywords: Cybersecurity, Data Encryption (DE), Access Control (AC), Intrusion Detection Systems (IDS), Cloud Security Compliance, Cloud Security Effectiveness.